If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1 + 3x = 2(x + -10) Reorder the terms: -1 + 2x + 3x = 2(x + -10) Combine like terms: 2x + 3x = 5x -1 + 5x = 2(x + -10) Reorder the terms: -1 + 5x = 2(-10 + x) -1 + 5x = (-10 * 2 + x * 2) -1 + 5x = (-20 + 2x) Solving -1 + 5x = -20 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -1 + 5x + -2x = -20 + 2x + -2x Combine like terms: 5x + -2x = 3x -1 + 3x = -20 + 2x + -2x Combine like terms: 2x + -2x = 0 -1 + 3x = -20 + 0 -1 + 3x = -20 Add '1' to each side of the equation. -1 + 1 + 3x = -20 + 1 Combine like terms: -1 + 1 = 0 0 + 3x = -20 + 1 3x = -20 + 1 Combine like terms: -20 + 1 = -19 3x = -19 Divide each side by '3'. x = -6.333333333 Simplifying x = -6.333333333
| 3(r+5)=30 | | -69=3x+2(5x-2) | | -2x-3(3x-10)=140 | | (n-8)*5=25 | | -2(5)+3y=-18 | | -720=x-9k | | 25x^2+10x+3=0 | | x-80=-11/8(y-0) | | 7(3x+2)2(1-x)+(3x+2)(1-x)3= | | 6y+9=28 | | x+2x+x-20=176 | | 10x-40y=0 | | 5x^2-12x+1=0 | | 16d+23=10d+39 | | 3x+5=3.5x+4 | | .33x=5 | | 30n=-90 | | 2(x+10)=5(3x+1) | | 6x^2+4x=3 | | y+4.2=2.4 | | 5.4=n/-0.9 | | r-5=6 | | 8x+25(3)=15x+20(2) | | (14-24)=6+4-9 | | -5/3+3/2 | | 7(3x+2)2(2-x)2+(3x+2)(1-x)= | | -3/2-3/5w=-5/3 | | -3(4-r)+r=2(4+r) | | 4(y+3)=2(y-7) | | (1+x)2(3x+2)(x+3)(x+5)= | | 88-2d=52+4d | | 5n+8=6n+19 |